Critical perspective of English teaching and learning in Turkey - Omer Gokhan Ulum; Kutay Uzun (International Journal of Evaluation and Research in Education (IJERE), 2020)
GTM (Grammar Translation Method) is still the commonly utilized method in EFL classes in Turkish Education System. Based on a phenomenographic research design, this paper inquires the personal constructs of EFL state school teachers (n= 15) on the related issue. There in lies the major result in that non-native EFL teachers, who have learnt English totally via GTM, teaches it via GTM as well. Implications are provided to overcome this vicious circle.